Characterizing Stellar and Gas Properties in NGC 628: Spatial Distributions, Radial Gradients, and Resolved Scaling Relations - Peng Wei; Hu Zou; Jing Wang; Xu Kong; Shuguo Ma; Ruilei Zhou; Xu Zhou; Ali Esamdin; Jiantao Sun; Tuhong Zhong; Fei Dang (The Astrophysical Journal)
Building on our previous research involving multiwavelength data from UV to IR, we employ spectroscopic observations of ionized gas, as well as neutral hydrogen gas obtained from the Five-hundred Meter Aperture Spherical Telescope (FAST), to explore the intrinsic processes of star formation and chemical enrichment within NGC 628. Our analysis focuses on several key properties, including gas-phase extinction, star formation rate (SFR) surface density, oxygen abundance, and H  i mass surface density. The azimuthal distributions of these parameters in relation to the morphological and kinematic features revealed by FAST H  i reveal that NGC 628 is an isolated galaxy that has not undergone recent interactions. We observe a mild radial extinction gradient accompanied by a notable dispersion. The SFR surface density also shows a gentle radial gradient, characteristic of typical spiral galaxies. Additionally, we find a negative radial metallicity gradient of −0.44 dex ${R}_{25}^{-1}$ , supporting the “inside-out” scenario of galaxy formation. We investigate the resolved mass–metallicity relation (MZR) and the resolved star formation main sequence (SFMS) alongside their dependences on the physical properties of both ionized and neutral hydrogen gas. Our findings indicate no secondary dependence of the resolved MZR on SFR surface density or H  i mass surface density. Furthermore, we observe that gas-phase extinction and the equivalent width of H α both increase with SFR surface density in the resolved SFMS.